2007
DOI: 10.1534/genetics.106.065888
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Zones Rather Than Molecular Forms Predict Genetic Differentiation in the Malaria VectorAnopheles gambiaes.s. in Ghana

Abstract: The malaria mosquito Anopheles gambiae s.s. is rapidly becoming a model for studies on the evolution of reproductive isolation. Debate has centered on the taxonomic status of two forms (denoted M and S) within the nominal taxon identified by point mutations in the X-linked rDNA region. Evidence is accumulating that there are significant barriers to gene flow between these forms, but that the barriers are not complete throughout the entire range of their distribution. We sampled populations from across Ghana an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 43 publications
8
48
0
Order By: Relevance
“…gambiae versus An. arabiensis comparisons; 2) most markers were already used successfully in unraveling intraspeciÞc spatial differentiation patterns (Donnelly and Townson 2000, Onyabe and Conn 2001, Yawson et al 2007; and 3) sample sizes were similar to previously published studies.…”
Section: Discussionsupporting
confidence: 57%
“…gambiae versus An. arabiensis comparisons; 2) most markers were already used successfully in unraveling intraspeciÞc spatial differentiation patterns (Donnelly and Townson 2000, Onyabe and Conn 2001, Yawson et al 2007; and 3) sample sizes were similar to previously published studies.…”
Section: Discussionsupporting
confidence: 57%
“…For example a recent paper by Yawson et al (2007) concluded that ecological barriers are more important to gene flow in Anopheles gambiae than geographical distance. Different genotypes may have different vector competencies, resulting in different disease incidences and hence priorities for mosquito or wetland management.…”
Section: Malariamentioning
confidence: 99%
“…The M and S molecular forms of An. gambiae s.s. represent incipient species (e.g., (Coluzzi et al 1985, Toure et al 1998, della Torre et al 2001, Favia et al 2001, Gentile et al 2001, Mukabayire et al 2001, Lehmann et al 2003, Turner et al 2005), but see (Lanzaro et al 1998, Yawson et al 2007). …”
Section: Introductionmentioning
confidence: 99%